An analysis of building energy submetering and its uses for colleges and universities - Sneed, Andrew (Kansas State University, 2022)
The intent of this report is to cover the topic of building energy submetering. Utilizing submeters to quantify building and sub-building energy usage can lead to reduced utility consumption, increased energy efficiency, lower operating costs, increased equipment longevity, improved occupant experiences, and also contribute to solving other issues. Additionally, submetering may be required to fulfill state and local building code requirements that have become more stringent over recent years, as well as to satisfy building benchmarking and energy audit requirements. This report identifies the needs, technologies, and benefits of providing energy submetering. While it generally covers these items, it also specifically applies them for colleges and universities that are comprised of multiple buildings with varying uses and energy demands. A case study is also provided for an actual university department in an existing building, identifying practical solutions and estimated costs for implementing a submeter system.
Keywords: Submetering; Energy; Benchmarking; Audit